2015
DOI: 10.1021/acs.jpcc.5b02297
|View full text |Cite
|
Sign up to set email alerts
|

Coverage Dependent Water Dissociative Adsorption on the Clean and O-Precovered Fe(111) Surfaces

Abstract: Water dissociative adsorption on the clean and Oprecovered Fe(111) surfaces at different coverage have been studied using the density functional theory method (GGA-PBE) and ab initio atomistic thermodynamics. On the clean p(3 × 3) Fe (111) surface, surface H, O, OH, and H 2 O species can migrate easily. Considering adsorption and H-bonding, the adsorbed H 2 O molecules can be dispersed or aggregated in close energies at low coverage, while in different aggregations at high coverage, indicating that the adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
9
12
0
Order By: Relevance
“…The CO molecules was adsorbed at the H n sites, and the E ads was lower than the same sites on the clean surface. The similar results were in agreement with some researchers who suggested that adsorbates always adsorb at the empty H sites of precovered Fe surface and the range of E ads for molecules are from −0.8 eV to −4.1 eV …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The CO molecules was adsorbed at the H n sites, and the E ads was lower than the same sites on the clean surface. The similar results were in agreement with some researchers who suggested that adsorbates always adsorb at the empty H sites of precovered Fe surface and the range of E ads for molecules are from −0.8 eV to −4.1 eV …”
Section: Resultssupporting
confidence: 93%
“…Because, for both kinds of metal‐precovered surfaces, most of the H 2 O molecules prefer vertical upward adsorption (Figure A), a little H 2 O molecules adsorb in a parallel (the plane of H 2 O is parallel to the surface, Figure B), vertical (the plane of H 2 O is vertical to the surface, and the center axis of O‐H bonds is parallel to the surface, Figure C), or tilted (the plane of O and H is vertical to the surface, and the center axis of O─H bonds is into a certain angle of surface, Figure Dd) direction related to the surface. Some reports have shown the similar results that the orientation of adsorbates relative to the surface was upward and parallel, vertical, and tilted . We can also see that the values are not obtained in Table for 3 adsorption sites on both surfaces, because the metal atoms assist H 2 O dissociation into the OH and H groups on these metal‐precovered surface.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…As a result, we carried out RPBE single-point energy calculation on the PBE optimized structure; and the computed CO adsorption energy is practically the same as found from RPBE optimization. [46][47][48] However, for the adsorption of H 2 O and H 2 on the Cu(111) surface, the computed adsorption energies are in excellent agreement with the available experimental data. Despite the excellent agreement in CO adsorption energy between experiment and RPBE computation, we are interested in the long-range dispersion corrections for van der Waals interaction.…”
Section: Methodssupporting
confidence: 74%
“…Shavorskiy et al [50] also found the formation of OH when water reacted with co-adsorbed O on the missing-row reconstructed Pt{110}(1ˆ2) surface. A similar promotion effect on the Fe(111) surface has been reported [51]. Hung et al [52] found that adsorbed oxygen facilitated water dissociation via the hydrogen transfer process on the pre-oxidized Fe(100) surface.…”
Section: Introductionsupporting
confidence: 69%